Immunity to Protozoan Parasites - Lopes, Marcela F. (2012)
Protozoan parasites cause several diseases, such as Malaria, Leishmaniasis, and Trypanosomiasis, hampering human development worldwide. Many protozoa cause infections that often follow chronic courses, owing to coevolution between parasites and host immune system. The survival and transmission of pathogenic protozoa depends on their ability to evade or subvert host’s innate and adaptive immune responses. A great challenge to research in immunology and parasitology is the development of strategies that favor immunity against protozoan parasites and prevent their evasion, chronic, or recurrent infections and associated pathologies. This special issue includes original papers and reviews that summarize current advances in our understanding on the mechanisms of immunity to protozoan parasites in humans and experimental animal models.